Analysis of Ocular Firework-Related Injuries and Common Eye Traumata: a 5-year Clinical Study - Frimmel, S.; Theusinger, O. M.; Kniestedt, C. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background A comparative study of eye injuries related to fireworks or acts of violence around New Yearʼs Eve and the Swiss National Day on August 1st. The two groups were compared with respect to the overall numbers of eye accidents within the period of review.Patients and Methods Retrospective analysis of emergency consultations at the Department of Ophthalmology, University Hospital Zurich with eye accidents around the Swiss National Day on August 1st and New Yearʼs Eve over the last 5 years. Two subgroups were formed: (1) Firework-related eye traumata, (2) Eye injuries due to acts of violence. The groups were analysed by age, gender, active participant or bystander, eye involved, severity of trauma (from clinical findings), surgical interventions, time of follow-up and visits, visual acuity and outcome.Results The study included 97 patients (100 eyes) with 74 male (76 %) and 23 female (24 %) victims. After filtering out 67 common traumata cases (all unilateral), 17 patients (18 eyes) with firework-related injuries and 13 patients (15 eyes) with damage due to an act of violence remained. Firework injuries accounted for 18 % of cases (65 % men); eye injuries caused by an act of violence accounted for 15 % of cases (92 % men). In the fireworks group, women were significantly older than men (mean age men 32 ± 14 years versus women 38 ± 16 years, p = 0.002). 65 % of cases were bystanders. The two subgroups contained 30 patients (33 eyes) with 22 left eyes (67 %, p < 0.001). The anterior segment was most frequently involved (79 %), significantly more often than the posterior part of the eye (p < 0.001). The posterior segment was injured more often in the fireworks group (28 %), than in the violence group (13 %). 87 % of the victims in the group of common traumata were mild trauma, 10 % moderate and 3 % severe. In the fireworks group the distribution was 53 % mild, 12 % moderate and 35 % severe, in the violence group 46 %, 23 % and 31 % respectively. Severe trauma cases occurred significantly more often around the New Year, with 36 % versus August 1st with 18 % (p = 0.0028). They are more often related to firework injuries than caused by violence (40 % versus 33 %). In summary, 7 victims (23 %) needed 8 interventions, with 3 having additional issues with their intraocular pressure. Full final visual acuity was noted in 88 %, which was alike in the two subgroups. On the contrary common traumata happened significantly more often around August 1st (66 %) than New Year (34 %; p < 0.001).Conclusions The number of injured eyes in the two subgroups of fireworks and violence was twice as high around New Yearʼs Eve than around the Swiss National Day. If the two events were combined, eye injuries were caused by an act of violence in 45 % and by fireworks in 55 % of cases. Injuries from fireworks can be decreased by professional fireworks. Both types of accident can be decreased by public awareness.
Keywords: firework; fireworks; eye trauma; eye injury; violence; public holidays; common eye traumata